Moses Outside the Torah and the Construction of a Diaspora Identity - Thomas Römer (Journal of Hebrew Scriptures, 2008)
This article deals with how, in texts inside and outside the Torah, Moses became a figure of identification for the different Jewish Diasporas during the Persian Period  The following themes are investigated: 1. The Shared Figure of Moses and the Pentateuch; 2. The death of Moses outside the land; 3. Moses, the magician; 4. Moses, the leprous; 5. Moses and the foreign women; 6. Moses, the warrior.